Fatty acid profile, oxidative status, and content of volatile organic compounds in raw and cooked meat of different chicken strains - A. Cartoni Mancinelli; E. Silletti; S. Mattioli; A. Dal Bosco; B. Sebastiani; L. Menchetti; A. Koot; S. van Ruth; C. Castellini (Poultry Science, 2021)
Chicken meat is rich in unsaturated fatty acids. Therefore, it is more susceptible to lipid oxidation and production of volatile organic compounds (VOC). In this study, we evaluated the fatty acids, antioxidants, and VOC profiles of raw and cooked meat samples derived from 4 strains of chicken differing in their growth rates, which were as follows: slow-growing (SG, Leghorn), medium-growing (MG, Hubbard and Naked Neck), and fast-growing (FG, Ross). The VOC profile of meat was measured using proton-transfer reaction–mass spectrometry (PTR–MS). The VOC were identified using PTR–time of flight-MS (PTR-ToF-MS). The data were analyzed using both univariate and multivariate models. Twenty main VOC were identified, which were classified into the following chemical categories: aldehydes, alkadienes, alkenes, furans, amides, alcohols, and other compounds. Our results revealed that the chicken genotype and the method of cooking strongly influenced the VOC profile of the meat. Identifying the relationships between these traits allowed us to highlight the trade-off of the main substrates such as n-3 and n-6 polyunsaturated fatty acids (PUFA), protective substances (antioxidants), and degradation products (VOC) of the poultry meat produced during cooking. The extent of VOC production and n-3 loss was found to be higher for the SG genotype. Reduction of n-6 was higher in MG, whereas small losses in antioxidants and PUFA were observed in the FG genotype, consequently, resulting in the lowest production of VOC. The SG and MG are genotypes more active from a kinetic point of view respect to the FG ones. For this reason, in the FG genotypes, the antioxidants are less involved in the oxidative stress induced by the movement; thus, they were available to protect the lipid of the meat during the cooking process. These results suggested that the use of SG and MG genotypes requires a specific dietary protocol (i.e., increasing the antioxidants content) to counteract the lipid oxidations in all the phases: in vivo, postmortem, and during/after cooking.